Substrates and potential therapeutics of ventricular arrhythmias in heart failure - Zhang, Dongze (Eur J Pharmacol, 2018)
Heart failure (HF) is a clinical syndrome characterized by ventricular contractile dysfunction. About 50% of death in patients with HF are due to fetal ventricular arrhythmias including ventricular tachycardia and ventricular fibrillation. Understanding ventricular arrhythmic substrates and discovering effective antiarrhythmic interventions are extremely important for improving the prognosis of patients with HF and reducing its mortality. In this review, we discussed ventricular arrhythmic substrates and current clinical therapeutics for ventricular arrhythmias in HF. Base on the fact that classic antiarrhythmic drugs have the limited efficacy, side effects, and proarrhythmic potentials, we also updated some therapeutic strategies for the development of potential new antiarrhythmic interventions for patients with HF.